Determination of Amount Poultry Farmers are ready to pay for Insurance: Evidence from Nigeria - Ojogbane, J. A.; Gbigbi, T.M. (International journal of Rural Development, Environment and Health Research, 2022)
The study x-ray the amount poultry farmers are ready to pay for insurance. Input-output data were collected from 120 farmers randomly selected from 10 communities. The data generated were subjected to descriptive and inferential statistics. The mean annual flock size per farmer before and after possession of insurance policy was 1255 Birds and 2247 Birds respectively. Investigation into the awareness level showed that more than half of the poultry farmers (83.3%) were aware of insurance. Around 56.7% of the respondents were ready to pay for insurance. The contributory factors of the amount farmers are ready to pay were education, income, awareness, experience and flock size. The major constraints affecting the readiness of farmers to pay for insurance were insufficient fund, high premium, size of farm and payment of indemnity. The readiness constraint index (WCI) was 79%.